Pelanggaran Etika Pariwara Indonesia dalam Iklan Dancow 1+ Imunonutri - Praditya, Radika Dava; Ramadhani, Dwi Ardika; Pamungkas, Alam Hanafi Assidiq Andi; Muktaf, Zein Mufarrih (Jurnal Audiens, 2025)
Advertisements are an effective communication tool to influence consumer behavior, including promoting the Dancow 1+ immunonutri formula milk product. However, advertising must meet the standards of the Indonesian Advertising Ethics to avoid misleading consumers. This research explores ethical violations in the "Dancow 1+ Imunonutri" advertisement, which was found to violate several articles in the Indonesian Advertising Ethics. Claims suggesting that consuming this product instantly can enhance children's intelligence, along with the use of dramatic visuals and price comparisons without supporting data, are considered misleading. This methodology uses qualitative descriptive analysis through advertisement observation and an advertising ethics approach. The analysis results show that the advertisement violates Article 1.29.3, which requires the delivery of clear and non-misleading information.